2009
DOI: 10.1186/1756-0500-2-186
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for caesarean wound infection in Lagos Nigeria

Abstract: BackgroundPost caesarean wound infection is not only a leading cause of prolonged hospital stay but a major cause of the widespread aversion to caesarean delivery in developing countries. In order to control and prevent post caesarean wound infection in our environment there is the need to access the relative contribution of each aetiologic factor. Though some studies in our environment have identified factors associated with post caesarean wound infection, none was specifically designed to address these issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
39
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 15 publications
12
39
2
2
Order By: Relevance
“…All analysis was carried out using the statistical software SPSS version 16 3,4,6 One of the patient related factors is young maternal age as most of the infections (92%) occurred in women less than thirty years of age, this is in accordance with other studies. 7,8 Hypertensive disorders in pregnancy which is linked with chronic alteration in peripheral blood supply have been found to a risk factor for SSI.9, 10 In this study 27.7% of patients with SSI suffered from this condition. Both obesity and malnutrition have been associated with increased risk of SSI.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…All analysis was carried out using the statistical software SPSS version 16 3,4,6 One of the patient related factors is young maternal age as most of the infections (92%) occurred in women less than thirty years of age, this is in accordance with other studies. 7,8 Hypertensive disorders in pregnancy which is linked with chronic alteration in peripheral blood supply have been found to a risk factor for SSI.9, 10 In this study 27.7% of patients with SSI suffered from this condition. Both obesity and malnutrition have been associated with increased risk of SSI.…”
Section: Methodsmentioning
confidence: 86%
“…Both obesity and malnutrition have been associated with increased risk of SSI. 7,8 The association of obesity with SSI could be due to relative avascularity of adipose tissue and hence poor healing, difficulty in handling of tissues and hence more chance of micro-trauma and also failure in obliteration of dead spaces. Likewise malnutrition can lead to SSI due to poor healing of tissues and decreased immunity.…”
Section: Methodsmentioning
confidence: 99%
“…When elective surgeries are undertaken, care should be taken to correct these factors before surgery. Oliver Ezechi et al [4] found factors like BMI > 25 kg/m 2 , anemia and prolonged operative time associated with increased incidence of post operative wound infection. All the gynecological surgeries were elective and so intra operative complications were significantly less in gynecological surgeries as compared to obstetric surgeries where a lot of surgeries were taken on emergency basis.…”
Section: Discussionmentioning
confidence: 99%
“…6,[9][10][11][12][13] This variation probably results from several factors in the various studies. [9][10][11][12][13] Firstly, studies with broad exclusion criteria have lower wound complication rates than studies with stringent exclusion criteria. The wound complication rate in our study was 7%, with the only exclusion criterion being declining to participate.…”
Section: Discussionmentioning
confidence: 99%